UIDSS2024_UID_Summer School 2024, Drawing for the Gods: Selinunte, Temple F (diségno, 2024)
This year too, UID promoted a new doctoral workshop which, as usual, focused on a specific theme, that is, an intensive training activity carried out over the course of a week, and in which doctoral students from various parts of Italy participated and were guided during the study days by various professors. [read more]